Modeling the relationship between digital nativity and Smartphone usage in learning English as a foreign language contexts - Hui, Lianghong; Teng, Lin Sophie; Guo, Fangfang (Frontiers in Psychology, 2023)
Despite many studies exploring the application of digital devices in foreign language learning, few studies have investigated the effect of the digital nativity on Smartphone usage in learning English as a foreign language (EFL) contexts. This research aims at filling the gap by exploring the relationships between EFL college students’ digital nativity and their use of Smartphones for English learning. The data were collected from 502 undergraduates in mainland China through self-reported questionnaires, namely the Digital Natives Assessment Scale and the Smartphone Use in Learning Foreign Language Scale. The confirmatory factor analysis validated a four-factor measurement model of digital nativity, including “grow up with technology”, “comfortable with multitasking”, “reliant on graphics for communication” and “thrive on instant gratification and rewards”. A second-order measurement construct of favorable Smartphone usage and its first-order adverse effects in foreign language learning were also examined, demonstrating good validity and reliability. The path analysis revealed that students who displayed more attributes of “grow up with technology” and “thrive on instant gratifications and rewards” tended to adopt smartphones for English learning positively. In addition, those who were more familiar with technological assistance might suffer less in the adverse effects of Smartphone usage. However, the preference for immediate responses and feedback could also lead to more adverse effects when using Smartphones for English learning. Besides, “comfortable with multitasking” and “reliant on graphics for communication” didn’t have significant predictive impact on either the favorable functions or the adverse effects of Smartphone usage.